Effect of Work Environment, Communication, and Organizational Culture on Job Satisfaction in PT. Sukses Maju Seketika - Stevanny Yap; Pujiarti Pujiarti (eCo-Buss, 2022)
The purpose of this study was to determine the impact of work environment, communication, and organizational culture on job satisfaction PT Sukses Maju Seketika.The population and sample for this study was 42 respondents. Collecting data from this study using a questionnaire to be distributed to respondents and processing data using SPSS 25. From the multiple linear regression, it is obtained the equation. The results of the multiple regression equation Y= -5.057+0.467 +0.407+0.270, meaning that every increase or decrease in the work environment (X1), Communication (X2), and Organizational Culture (X3) is 1 point, then satisfaction work (Y) at PT. Success Forward will increase or decrease by 0.467, 0.407, and 0.207. Based on the hypothesis test, t value for the working environment (X1) is 4.629, communication (X2) is 3.258, and organizational culture (X3) is 2.443. The value of the t table is 1.68488. So it can be concluded that Ho is denied and Ha is accepted, because t count > t table. While the results of the F test obtained the calculated F value of 81.112 with a significant level of 0.000 where the calculated F is greater than the F table of 2.85. Thus Ho is denied and Ha is accepted, because F count > F table and is significantly smaller than 0.05.